Genetic polymorphisms of antioxidant enzymes (GSTP1/CAT/HMOX1/EPHX1) and childhood asthma risk in Fuzhou - Wu, Ziling; Chen, Qiaobin; Lin, CaiChun; Huang, HongBiao; Chen, Lang (Frontiers in Pediatrics, 2025)
ObjectiveDiscuss the correlation between single nucleotide polymorphisms (SNPs) of the Glutathione s-transferase Pi-1 (GSTP1), Catalase (CAT), Heme oxygenase-1 (HMOX1), and Homo sapiens epoxide hydrolase 1 (EPHX1) genes and the risk of childhood asthma in Fuzhou.MethodsNext generation sequencing (NGS) was employed to conduct whole-exome sequencing (WES) on 50 asthmatic children and 50 healthy children. Genetic models for the GSTP1 gene rs1695, rs4891, HMOX1 gene rs2071747, rs17878790, CAT gene rs7943316, rs1049982, rs769217, and EPHX1 gene rs2234922, rs41266231, rs1051740 sites were constructed. Binary logistic regression, linkage disequilibrium analysis, haplotype analysis, and interaction analysis were used to study the correlation between the 10 SNPs of GSTP1, CAT, HMOX1, and EPHX1 genes and the risk of asthma in children in the Fuzhou region.ResultsThe rs1695 A>G variant increased the risk of asthma in the heterozygous, dominant, and allele models. The rs4891 T>C variant increased the risk of asthma in the heterozygous, dominant, and allele models. The rs7943316 A>T variant increased the risk of asthma in the homozygous, recessive, and allele models. The rs769217 C>T variant decreased the risk of asthma in the homozygous, recessive, and allele models. Strong linkage disequilibrium between the GSTP1 gene rs1695 and rs4891, and the CAT gene rs7943316, rs1049982, and rs769217. The GC haplotype composed of GSTP1 gene rs1695 and rs4891 may pose a risk for childhood asthma [P = 0.025, OR = 2.12 (1.09–4.10)], while the AT haplotype may be protective [P = 0.025, OR = 0.47 (0.24–0.92)]. The ATT haplotype composed of CAT gene rs7943316, rs1049982, and rs769217 may be protective against childhood asthma [P = 0.006, OR = 0.45 (0.25–0.79)]. Potential synergistic interaction between the GSTP1 gene rs1695, CAT gene rs7943316, and EPHX1 gene rs41266231. The combination of GSTP1 gene rs1695 and CAT gene rs7943316 formed the best predictive model for assessing the risk of childhood asthma in the Fuzhou region.ConclusionThe genotype GC, composed of GSTP1 gene rs1695 and rs4891, may represent a risk genotype for childhood asthma, whereas genotype AT may represent a protective genotype for childhood asthma. The genotype ATT, composed of CAT gene rs7943316, rs1049982, and rs769217, may represent a protective genotype for childhood asthma. The combination of GSTP1 gene rs1695 and CAT gene rs7943316 constitutes the optimal model for predicting the risk of childhood asthma in the Fuzhou region.